Pemanfaatan Keanekaragaman Bambu Secara Hidrologis, Ekonomis, Sosial dan Pertahanan - Revi Mainaki; Rendra Zainal Maliki (Geodika: Jurnal Kajian Ilmu dan Pendidikan Geografi, 2020)
Indonesia is one of countries with a relatively high level of biodiversity. One of these biological resources, is bamboo. The existence of bamboo plants in Asia, including Indonesia, is widely used by segments, reeds, midribs, colors and height for various purposes. The writing of this article aims to explain the use of bamboo diversity in a hydrological, economic, social and defense manner in society, as one of the alternative solutions for the utilization of biological resources in Indonesia. The type of data used is literature data in the form of scientific papers or relevant research results. The data that has been collected is then analyzed using a qualitative descriptive approach. The results showed: 1) the hydrological function of bamboo provides direct benefits as a conservation plant reducing erosion, preventing landslides, good land cover for water catchments, while indirectly as a support for the population's water needs such as pipes, canals and water containers; 2) the economic function of bamboo helps to support human needs, increase income and open up new economic opportunities such as building construction materials, plaits, concrete bones, ropes, connecting tools, roofs, floors and bridges; 3) The social function of bamboo is to trigger social activities between individuals or community groups, such as the use of bamboo for musical instruments, eye drops, fishing rods, nurseries, rafts and cigarette pipes; and 4) The function of bamboo defense itself is closely related to the history of the Indonesian people, especially as a weapon in the fight against invaders, in addition to the function of bamboo defense itself, namely as a defense field and live and artificial fences.